Genome-informed integrative taxonomic description of three cryptic species in the earthworm genus Carpetania (Oligochaeta, Hormogastridae). Issue 3 (2nd April 2020) - Marchán, Daniel Fernández; Fernández, Rosa; Domínguez, Jorge; Díaz Cosín, Darío J.; Novo, Marta
Abstract : Research on cryptic species complexes has reached a consensus on the necessity of integrating multiple sources of evidence. Reduced representation library techniques such as Genotyping-by-Sequencing (GBS) have proven useful to study these groups. Both integrative taxonomy and genome-wide single nucleotide polymorphism (SNP) data remain to be widely applied to earthworms, an animal group with widespread presence of cryptic diversity. The genus Carpetania (formerly the Hormogaster elisae species complex) was found to contain six deeply divergent genetic lineages and some inconspicuous morphological differentiation based on a handful of Sanger-sequenced markers. Marchán et al. (submitted) delimited three well-supported species-level clades on the basis of a genome-wide SNP dataset and geometric morphometric analyses, highlighting the necessity of a formal taxonomic description of these taxa. In this work, further analyses are applied to the SNP data and a thorough morphological study is performed in order to provide an integrative description of two new species and to redescribe Carpetania elisae . Species-specific SNPs are identified and used as diagnostic characters, and genome-wide and cytochrome oxidase C subunit 1 (COI) genetic distances are compared finding a strong correlation between them. The taxonomic description of these three cryptic species provides a useful tool to include them effectively in ecological studies and biodiversity conservation actions. www.zoobank.org/urn:lsid:zoobank.org:act:19CC41D7-BD25-4337-BED5-CDB04CAFB537 www.zoobank.org/urn:lsid:zoobank.org:act:206EE090-4AF5-4D12-82CA-F4A6494E90D4 www.zoobank.org/urn:lsid:zoobank.org:pub:2797FDDF-EA3D-4347-96C6-E632DC26CDA3